anonymous
  • anonymous
How do you calculate new functions from old ones using table quantities (x, f(x), g(x), f'(x), g'(x))?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Do you have a specific question? It might be easier to help you with more details.
anonymous
  • anonymous
yes there's a table that goes along with it.
anonymous
  • anonymous
yes there's a table that goes along with it.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

jim_thompson5910
  • jim_thompson5910
@tigel__ post the screenshot of the full problem please
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
The third one's the easiest by a slight margin. \[\frac{f(-2)}{g(-2)+5}=\frac{23}{13+5}\] Do you see how I got that?
anonymous
  • anonymous
The second one could come next. Recall that \((fg)(x)=f(x)g(x)\), so \[(fg)(4)=f(4)g(4)=-97\times25\] For the other two, you'll need to take derivatives. By the product rule (for the fourth problem): \[(fg)'(-2)=f'(-2)g(-2)+f(-2)g'(-2)=-32\times13+23\times(-10)\] By the chain rule (for the first one): \[h'(4)=\bigg(g(f)\bigg)'(4)=g'(f(4))f'(4)=g'(-97)f'(4)=\cdots\] Does that make sense?
anonymous
  • anonymous
No I'm confused. on the first one
jim_thompson5910
  • jim_thompson5910
@tigel__ the one where you put -9700 ?
anonymous
  • anonymous
yes
jim_thompson5910
  • jim_thompson5910
(fg)(x) = (f*g)(x) (fg)(x) = f(x)*g(x) (fg)(4) = f(4)*g(4) (fg)(4) = -97*25 (fg)(4) = -2425
jim_thompson5910
  • jim_thompson5910
I got f(4) and g(4) from the table look in the f(x) row and column that starts with 4 to get f(4) similar for g(4)
anonymous
  • anonymous
Oh im sorry! I meant the other one the one above it,
jim_thompson5910
  • jim_thompson5910
oh ok
jim_thompson5910
  • jim_thompson5910
h(x) = g(f(x)) h ' (x) = g ' (f(x)) * f ' (x) ... chain rule h ' (4) = g ' (f(4)) * f ' (4) ... replace every x with 4 h ' (4) = g ' (-97) * f ' (4) ... use the table h ' (4) = (-390) * (-80) ... use the table h ' (4) = 31,200
jim_thompson5910
  • jim_thompson5910
f(4) = -97 f ' (4) = -80 g ' (-97) = -390

Looking for something else?

Not the answer you are looking for? Search for more explanations.